2013
DOI: 10.1016/j.jfma.2013.06.019
|View full text |Cite
|
Sign up to set email alerts
|

Clinical characteristics of central diabetes insipidus in Taiwanese children

Abstract: Because a delayed diagnosis of CDI is common in Taiwanese children, a high index of suspicion is important. The underlying etiology of CDI in children may not initially be obvious. Long-term surveillance is therefore necessary, especially for the early detection of evolving treatable intracranial lesions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
8
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 19 publications
2
8
2
Order By: Relevance
“…In our cohort, the causes of SSR lesions only included GCT, LCH and CP, whose proportions were 74.5, 18.2, and 7.3%, respectively. Liu et al (14) also found that GCT was the most common cause (52.6%) among acquired infiltrative disease or tumor in Taiwanese children with CDI, which was consistent with our results. This might indicate that GCT would be the most likely to invade the hypothalamic- (13), the proportion of GCT among acquire infiltrative disease or tumor was much lower (21.3, 21.1, and 26.7%, respectively).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In our cohort, the causes of SSR lesions only included GCT, LCH and CP, whose proportions were 74.5, 18.2, and 7.3%, respectively. Liu et al (14) also found that GCT was the most common cause (52.6%) among acquired infiltrative disease or tumor in Taiwanese children with CDI, which was consistent with our results. This might indicate that GCT would be the most likely to invade the hypothalamic- (13), the proportion of GCT among acquire infiltrative disease or tumor was much lower (21.3, 21.1, and 26.7%, respectively).…”
Section: Discussionsupporting
confidence: 93%
“…Previous studies about pediatric CDI mainly focused on etiology and common features, while our study mainly focused on CDI caused by SSR lesions, and summarized the detailed clinical manifestations, tumor markers, radiology characteristics and histopathology about each etiology, trying to offer evidence for diagnosis and differential diagnosis. Acquired infiltrative disease or tumor including CP, GCT, LCH, pituitary adenoma, lymphoma, astrocytoma, and cavernous hemangioma were all the etiology of CDI reported before (9,(11)(12)(13)(14). In our cohort, the causes of SSR lesions only included GCT, LCH and CP, whose proportions were 74.5, 18.2, and 7.3%, respectively.…”
Section: Discussionmentioning
confidence: 70%
“…Dysfunction of the anterior pituitary can be determined at diagnosis and during the follow-up period of CDI. In the present study, 53.5% of the patients had anterior pituitary hormone deficiency when CDI was diagnosed, which was lower than the 80% reported by Liu et al [ 29 ]. Most of these patients had growth hormone deficiency, not related to etiology.…”
Section: Discussioncontrasting
confidence: 82%
“…[ 18 ] Germ cell tumors and Langerhans cell histiocytosis (LCH) accounted for 60% of CDI cases in Taiwanese children, and histiocytosis accounted for 18.6% of cases in Indian children. [ 16 19 ] LCH as a cause of CDI has been associated with better survival. [ 17 ]…”
Section: T Ypes Of D Iabetes I mentioning
confidence: 99%